Modeling two-phase flow in pipe of the solar collector (International Journal of Mathematics and Physics, 2018)
Abstract. Solar collector is often used as evaporator in heat pump system. In the solar collector pipe, liquid is transferred from liquid phase to gas phase. The effective operation of heat pump depends on boiling point of the refrigerant and the process of phase change. Therefore, simulation of two-phase flow in the pipe is considered. In two-phase flow, velocity field and pressure of the liquid phase are characterized by incompressible Navier-Stokes equation and compressible Navier-Stokes equation in the vapor phase. Dynamics of two-phase flow is described by Cahn-Hilliard equation to take into account the phase transition. Two-phase flow is solved using finite elements in COMSOL Multiphysics program using phase-field model based on Cahn-Hilliard phase variable equation. The higher the liquid density, the higher the Archimedes force on the vapor, which is the prerequisite for rapid and intense rise from the vapor bubbles. This also explains why the value of oscillation is bigger. This article discusses the two-phase flow of solar collector coolant. Therefore, it is desirable to select the density value so that the liquid is rapidly steamed and fast, i.e., it has low oscillation. Based on these results, we can describe the effect of the liquid phase (density) on phase transitions.   GMT АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский        Звуковая функция ограничена 200 символами  Настройки : История : Обратная связь : DonateЗакрыть